2015
DOI: 10.1007/s00500-015-1590-z
|View full text |Cite
|
Sign up to set email alerts
|

Using a branch-and-bound and a genetic algorithm for a single-machine total late work scheduling problem

Abstract: Scheduling with learning effects has received a lot of research attention lately. On the other hand, it is commonly seen that time restrictions are usually modeled by due dates or deadlines and the quality of schedules is estimated with reference to these parameters. One of the performance measures involving due dates is the late work criterion, which is relatively unexplored. Thus, we study a single-machine scheduling problem with a position-based learning effect. The objective is to minimize the total late w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…. , m. More results on scheduling with late work criteria can be found in Blazewicz and Finke [2], Blazewicz et al [3] , Chen and Yuan [4], Chen et al [6,7], Freud and Mosheiov [8], He et al [11], Kethley and Alidaee [13], Leung [16], Mosheiov et al [20], Ren et al [23,24], Sterna [25,26], Wu et al [29], and Xu et al [30].…”
Section: • Ymentioning
confidence: 99%
“…. , m. More results on scheduling with late work criteria can be found in Blazewicz and Finke [2], Blazewicz et al [3] , Chen and Yuan [4], Chen et al [6,7], Freud and Mosheiov [8], He et al [11], Kethley and Alidaee [13], Leung [16], Mosheiov et al [20], Ren et al [23,24], Sterna [25,26], Wu et al [29], and Xu et al [30].…”
Section: • Ymentioning
confidence: 99%
“…Using these techniques in scheduling makes an allowance for us to test problems with a large number of jobs. Minimizing the total late work on a single machine was treated by Chin-Chia Wu [2]. where he proposed three genetic algorithms and combined them to get the fourth one, his computational results showed that the three (GA) algorithms were getting the stability state when n becomes larger.…”
Section: Alaa Sabah Hameedmentioning
confidence: 99%
“…Therefore, the total late work criterion is minimized to account for the minimum late parts of each customer's order. This criterion has been applied on single machine scheduling 28,29 , resource constrained project scheduling 30 , identical parallel processors scheduling 31 , flow shop scheduling [32][33][34][35] , open shop scheduling 36 , and flexible manufacturing scheduling. 37 Interested readers on the late work criterion can refer to a state-of-the-art literature survey performed by Sterna.…”
Section: Literature Reviewmentioning
confidence: 99%